Educação Audiovisual da Sexualidade: olhares a partir do Kit Anti-Homofobia - Silva, Ricardo Desidério da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sexual Education as a continuous action should be developed in a process of human interaction by which, inserted in a culture, a history and a politic, leads us to think in a building of an active subject front the informations, the desires, the basic needs of their body and the eroticism. The Sexual Education in the school is necessary to be made both in political discussions, as in practical actions, when one thinks about the school as a crop production space; it aims to be an effective proposal, where there is objective and relevant content, appropriate methodologies such as the use of video as a teaching resource that provides reflections that allow discussions on the topic of sexuality. In this sense, we propose a new perception of the images and sounds study: audiovisual sexuality education, analyzing here the videos Anti-Homophobia Kit. Therefore, this study aimed to describe and critically analyze the videos that make up the DVD Torpedo, part of the material of the Anti- Homophobia Kit, aimed at the possibility of their use as educational material on sexual education projects at school. This is a descriptive qualitative research, document type. Were selected and analyzed the videos: Torpedo, Encontrando Bianca and Probabilidade, from a general description of their content, form and imageries, organized into two thematic categories: (1) Sexism and heteronormativity in school and in the family and (2) Looks for subjectivity. In this process, was noticeable that the videos reaffirm stereotypes and build the foundation for the establishment of what is considered acceptable, normal and what is different and what to exclude. Examples such as the targeting of children in sports activities, as well as the explicit violence (bullying), the homophobia, the lesbophobia and the transphobia, suffered by some of the characters leaves us clear the absence of an adult figure in the interlocution of these acts. In addition, it was noted ...

A Educação Sexual enquanto ação contínua deve ser desenvolvida num processo de interação humana pelo qual, inserido em uma cultura, uma história e uma política, nos leva a pensar na construção de um sujeito ativo frente às informações, aos desejos, às necessidades básicas sobre seu corpo e erotismo. A Educação Sexual na escola é uma necessidade a ser efetivada tanto nas discussões políticas, quanto nas ações práticas quando se pensa na escola enquanto um espaço de produção de cultura; nela se almeja uma proposta eficaz em que haja objetivos e conteúdos pertinentes, metodologias adequadas, como a utilização de vídeos como recurso pedagógico que proporcione reflexões que possibilitem debates sobre a temática da sexualidade. Neste sentido, propõe-se uma nova percepção do estudo de imagens e sons: a educação audiovisual da sexualidade, partindo aqui dos vídeos do Kit Anti-Homofobia. Para tanto, este estudo teve por objetivo descrever e analisar criticamente os vídeos que compõem o DVD Torpedo, parte integrante do material do Kit Anti-Homofobia, visando a possibilidade de sua utilização como material educativo em projetos de Educação Sexual na Escola. Trata-se uma pesquisa qualitativa descritiva, tipo documental. Foram selecionados e analisados os vídeos Torpedo, Encontrando Bianca e Probabilidade, a partir de uma descrição geral de seu conteúdo, forma e imagens, organizada em duas categorias de conteúdo temáticas: (1) Sexismo e heteronormatividade na escola e na família e (2) Olhares para subjetividade. Nesse processo, foi possível notar que os vídeos reafirmam estereótipos e constroem as bases para o estabelecimento do que é considerado como aceitável, normal, e do que é diferente e que deve ser excluído. Exemplos como a segmentação de meninos e meninas nas atividades esportivas, assim como a violência explícita (bullying), a homofobia, lesbofobia e...
Audiovisual Sexuality Education: views about the Anti- Homophobia Kit
Keywords: Educação sexual; Educação sexual - Recursos audiovisuais; Educação sexual para crianças; Homofobia - Educação; Education